2014
DOI: 10.1016/j.otsr.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Missed diagnosis of false aneurysm of the superficial femoral artery after closed complex fracture of the distal femur

Abstract: This case report presents a 38-year-old male patient who developed a false aneurysm of the superficial femoral artery after minimally invasive plate internal fixation of a comminuted articular distal femoral fracture sustained in a motor vehicle accident. Two days after surgery, the patient developed pain, non-pulsatile swelling on the medial side of the knee and anemia. After about six weeks, diagnosis of false aneurysm of the superficial femoral artery was confirmed by duplex ultrasound and computed tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…With the increasing incidence of proximal femoral fractures, the need to pay attention to the treatment of complications has also increased [ 7 ]. Iatrogenic vascular injuries are more severe complications and are difficult to diagnose early [ 8 ]. Understanding the anatomical relationship between the femur and femoral artery along with its branches is critical in preventing iatrogenic vascular injuries.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing incidence of proximal femoral fractures, the need to pay attention to the treatment of complications has also increased [ 7 ]. Iatrogenic vascular injuries are more severe complications and are difficult to diagnose early [ 8 ]. Understanding the anatomical relationship between the femur and femoral artery along with its branches is critical in preventing iatrogenic vascular injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The latter includes sharp bone fragments, scar tissue, and direct trauma (open injuries), whereas the former consists of insertion plate screws or locking bolts of intramedullary nails, and also malpositioned retractors, plunging drill bits, and the movements of fragments during reduction procedures. 13,14 Manner et al emphasized that traction on a fracture table tightens the femoral muscles and additionally reduces the local mobility of the DFA. 15 Yang et al demonstrated the influence of the extremity's position on the fracture table on the distances between femoral vessels and the medial femoral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing incidence of PFF draws more attention to treatment and relevant complications [1,13,14], of which iatrogenic vascular injury is a severe complication and is difficult to diagnose early [15,16]. Identifying the relationship between femoral arteries and femur in the medial aspect of the femur is critical for prevention of iatrogenic vascular injury in internal fixation of PFF.…”
Section: Discussionmentioning
confidence: 99%